PERBEDAAN KADAR TRIGLISERIDA WANITA SEBELUM DAN SESUDAH TERAPI BEKAM - Sinaga, Diana Fransiska; Welkriana, Putri Widelia; Farizal, Jon (Politeknik Kesehatan Kemenkes Bengkulu, 2019)
Background: Wet cupping therapy can excavate the hydrophilic and hydrophobic material one example is lipoprotein. Triglycerides are used as blood biochemical parameters to determine the interference of fat metabolism. Hypertriglyceridemia is a condition that occurs because of increased triglyceride levels that trigger the accumulation of lipids in the walls of the arteries that can cause atherosclerosis. Objective: This research is to know the difference of triglyceride level of women before and after cupping therapy at Cottage Alternative Medicine Miftahussyifa Bengkulu City. Methods: The research conducted is Analytical. The research design used was researched design pre-experimental with one group pre-post test. The sample in this study were 32 respondents by using purposive sampling method. Samples were measured by method clinical analyzer using a clinical analyzer instrument (Architect Plus C4000®) and using triglyceride reagent (proliferation Abbot Architect Plus C4000®). Results: This study showed that of 32 female respondents who had first followed bruise therapy then examined triglyceride levels before and after cupping therapy with the first venous blood taking done before the cordoning, the second venous blood taking was done immediately after the curing of the same sample. The result showed that the mean of triglyceride level before and after cupping therapy decreased with the mean value of triglyceride level before cupping therapy 208,28 mg / dL and mean value of triglyceride level after cupping therapy 200,59 mg / dL. The result of T-test analysis is dependent with value p =0,002 (p <0,05). Conclusion: There are significant differences in triglyceride levels before and after cupping therapy at Cottage Alternative Medicine Miftahussyifa Bengkulu City.